Extended Editor's Report: IFLA Notes from Robin Kear. Issue 4 (1st October 2016) - Kear, Robin L.
From The Column Editors: Welcome to the Global Postcards column! We are so excited to bring you news and projects from around the world. We have three main contributions for this column: Heather Moulaison Sandy reports on LIDA in Croatia, Molly Brown shares her experiences with user experience and space planning, and Kathryn McNamara shares her impressions of IFLA as a first-time attendee. Thanks to the contributors for this issue, and please keep the submissions coming! If you would like to send a submission, please contact either of the column's co-editors: Jacqueline Solis, jsolis@email.unc.edu, and Robin Kear, rlk25@pitt.edu. ABSTRACT: I attended the IFLA WLIC 2016 in Columbus, OH from August 12 to 19 and started a 2-year IFLA International Leadership Program. The other eight members of the cohort are from China, Colombia, Egypt, Latvia, Mexico, the Philippines, Senegal, and Serbia. We had a full conference and tweeted about it at #IFLAILP2. I will be working with two other members of the cohort and a mentor in the area of 'access to digital content' projects, on topics like open access, e-lending across borders, copyright, and Wikipedia. I would like to recap the best sessions that I attended at the conference related to digital content.